Design and fabrication of carbon fiber/carbonyl iron core–shell structure composites as high-performance microwave absorbers. Issue 12 (11th February 2015) - Yuan, Liu; Xiangxuan, Liu; Rong, Li; Wu, Wen; Xuanjun, Wang
<x xml:space="preserve">Abstract</x> Carbon fiber/carbonyl iron core–shell structure composites with excellent microwave absorbing performance were prepared by a metal organic chemical vapor deposition process.